Effect of Ingested Liquids on Color Change of Composite Resins - Beheshteh Malek Afzali; Amir Ghasemi; Asrin Mirani; Zahra Abdolazimi; Alireza Akbarzade Baghban; Mohammad Javad Kharazifard (Tehran University of Medical Sciences, 2016)
Objectives: Color change of composite restorations is well known to dentists. However, the effect of commonly consumed drinks on discoloration of composite resins has yet to be determined. This study sought to assess the color change of a nanofilled (Premise) and a flowable composite resin (Premise flowable) following simulated consumption of tea, cola, iron drops and multivitamin syrup. Materials and Methods: Forty disk-shaped specimens (7 mm in diameter and 2 mm thick) were fabricated from each composite resin. The baseline color values were measured according to the CIE L*a*b* system using digital imaging. The specimens of each restorative material were randomly divided into five groups (eight each) according to the storage media namely tea, cola, iron drops, multivitamin syrup or distilled water (control). The specimens were immersed in staining solutions for three hours daily over a 40-day test period. Following this, the color change values (ΔE*) were calculated. For statistical analyses, the color differences were analyzed using two-way ANOVA and Tukey's test (P< 0.05). Results: There was no significant difference in ΔE* values between the two types of composite resins (P>0.05). In both composite materials, the difference among the solutions was not significant (P>0.05).  Conclusion: Under the tested experimental conditions, both restorative materials were susceptible to discoloration by all four staining solutions. The color change values were not related to the solution or the type of material used.